Optimalisasi Pembuatan Arang Briket yang Berkualitas dengan Metode Multi Factor Evaluation Process (MFEP) (International Forum of Researchers and Lecturers, 2025)
This research optimises the production of quality charcoal briquettes using the Multi Factor Evaluation Process (MFEP) method to meet the need for sustainable alternative energy. The main raw material is coconut shells, which are cleaned, burned in iron drums, and sun-dried to produce quality charcoal. Quality evaluation was conducted on calorific value, moisture content, ash content, and compressive resistance. Findings showed significant improvement in the quality of briquetted charcoal after the application of MFEP, with higher calorific value, lower moisture and ash content, and better compressive resistance. This research supports energy efficiency, reduces emissions, and improves environmental sustainability and community welfare.